Out of the periphery : development of coastal chars in Southeastern Bangladesh - Wilde, Koen de. (Dhaka : University Press Limited, 2000)
On the development of newly accreted land in the southeastern part of Bangladesh.
Includes index.
ARC, GenEd
Book Finder International
BRAC University
Keywords: Regional planning -- Bangladesh; Economics; Bangladesh -- Economic policy